2019
DOI: 10.1007/s42454-019-00002-x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling human cognition of abnormal machine behaviour

Abstract: Despite the advances in intelligent systems, there is no guarantee that those systems will always behave normally. Machine abnormalities, unusual responses to controls or false alarms, are still common; therefore, a better understanding of how humans learn and respond to abnormal machine behaviour is essential. Human cognition has been researched in many domains. Numerous theories such as utility theory, three-level situation awareness and theory of dual cognition suggest how human cognition behaves. These the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 129 publications
(176 reference statements)
1
18
0
Order By: Relevance
“…2. DCAM also supports the opportunities identified in a previous study (Illankoon et al 2019c) to model the cognition of abnormal machine behavior using a combined approach along two dimensions: broad types of knowledge (i.e., explicit-implicit) and broad levels of agents (i.e., human-intelligent systems). In the next sections, we discuss how the DCAM can overcome the two major limitations of the present models: limited focus on dynamics, and limited focus on perceptual-cognitive tasks.…”
Section: A New Model: Distributed Collaborative Awareness Model (Dcam)supporting
confidence: 77%
See 1 more Smart Citation
“…2. DCAM also supports the opportunities identified in a previous study (Illankoon et al 2019c) to model the cognition of abnormal machine behavior using a combined approach along two dimensions: broad types of knowledge (i.e., explicit-implicit) and broad levels of agents (i.e., human-intelligent systems). In the next sections, we discuss how the DCAM can overcome the two major limitations of the present models: limited focus on dynamics, and limited focus on perceptual-cognitive tasks.…”
Section: A New Model: Distributed Collaborative Awareness Model (Dcam)supporting
confidence: 77%
“…MDS model should consider both the different levels of automation (Parasuraman et al 2000) offered by a decision support system and the wide modes of human cognition involved in gaining situation awareness of machine behaviors (Illankoon et al 2019c). Accordingly, in the DCAM, the internal problem representation is identified as a continuum between two poles: explicit and implicit knowledge.…”
Section: From Explicit To Implicit Collaborationmentioning
confidence: 99%
“…Computer systems and any device that operates on software and has access to a network are on target, vulnerable, and thereby open to exploit, misuse, and manipulation. Abnormal behaviors (Illankoon et al 2019), data access interruptions, delays, data modifications, fabrications, losses, leakages, or other problems in these systems and devices emanate from both human and nonhuman motives and causes. Such motives and causes, in general terms, consist of user error, defects in code, malicious acts, hardware failure, and acts of nature (Strebe 2002).…”
Section: Identifying the Main Characteristics Of I-hrmmentioning
confidence: 99%
“…Previous studies have shown SA applicability in maintenance (e.g. Illankoon et al 2019c). In this paper, using case studies, we tested the hypothesis "SA intervention can rectify the judgemental errors in maintenance".…”
Section: Interventions For Judgemental Biasesmentioning
confidence: 98%